k = 1 ∑ 1 5 cis 2 k − 1 ( 3 6 π )
Compute the imaginary part of the summation above.
Notation
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How did you get the motivation to multiply both sides by -2sin?
Log in to reply
Roni... try this problem:
https://brilliant.org/problems/day-7-seven-terms-in-a-tricky-trig-sum/?group=R7BPCpcARbs3&ref_id=1049242
;-)
We note that cis θ = c o s θ + i sin θ = e i θ . Therefore,
k = 1 ∑ 1 5 cis 2 k − 1 3 6 π = k = 1 ∑ 1 5 e i 3 6 ( 2 k − 1 ) π This is a GP with first term e i 3 6 π and common ratio e i 1 8 π = 1 − e i 1 8 π e i 3 6 π ( 1 − e i 1 8 1 5 π ) = 1 − cos 1 8 π − i sin 1 8 π ( cos 3 6 π + i sin 3 6 π ) ( 1 − cos 6 5 π − i sin 6 5 π ) = ( 1 − cos 1 8 π − i sin 1 8 π ) ( 1 − cos 1 8 π + i sin 1 8 π ) ( cos 3 6 π + i sin 3 6 π ) ( 1 − cos 6 5 π − i sin 6 5 π ) ( 1 − cos 1 8 π + i sin 1 8 π ) = ( 1 − cos 1 8 π ) 2 + sin 2 1 8 π ( cos 3 6 π + i sin 3 6 π ) ( 1 + 2 3 − i 2 1 ) ( 1 − ( 1 − 2 sin 2 3 6 π ) + i 2 sin 3 6 π cos 3 6 π ) = 2 − 2 cos 1 8 π ( cos 3 6 π + i sin 3 6 π ) ( 2 + 3 − i ) sin 3 6 π ( sin 3 6 π + i cos 3 6 π ) = 4 sin 2 3 6 π sin 3 6 π ( 2 + 3 − i ) ( cos 3 6 π sin 3 6 π − sin 3 6 π cos 3 6 π + i ( sin 2 3 6 π + cos 2 3 6 π ) ) = 4 sin 3 6 π 1 + i ( 2 + 3 )
⇒ ℑ ( k = 1 ∑ 1 5 cis 2 k − 1 3 6 π ) = 4 sin 3 6 π 2 + 3
Mr Cheong, you really are the trigonometry god!!!
Log in to reply
Not really. You may Brian Charlesworth better. I am glad that you like the solution.
Log in to reply
I really like how you lay down your solutions Mr Cheong.. you are a living legend and I am grateful to have lived and see it :) Keep it up..
Let w = e π i / 3 6 . Then let S = k = 1 ∑ 1 5 w 2 k − 1 . Using the formula for the sum of a geometric progression we have:
S = w − 1 k = 1 ∑ 1 5 w 2 k = w − 1 ⋅ w 2 − 1 w 3 2 − w 2 = w 2 − 1 w 3 1 − w
Now, simplify and rationalize the denominator:
S = ( w 2 − 1 ) ( w − 2 − 1 ) ( w 3 1 − w ) ( w − 2 − 1 ) = 1 − w 2 − w − 2 + 1 w 2 9 − w 3 1 − w − 1 + w = 2 − 2 cos ( 1 8 π ) w 2 9 − w 3 1 − w − 1 + w
Finally, find the real part and the imaginary part, and simplify the denominator using the identity sin ( 2 θ ) = 2 1 − cos θ :
S = 4 sin 2 ( 3 6 π ) cos ( 3 6 2 9 π ) + i sin ( 3 6 2 9 π ) − cos ( 3 6 3 1 π ) − i sin ( 3 6 3 1 π ) − cos ( 3 6 π ) + i sin ( 3 6 π ) + cos ( 3 6 π ) + i sin ( 3 6 π )
S = 4 sin 2 ( 3 6 π ) cos ( 3 6 2 9 π ) − cos ( 3 6 3 1 π ) + i sin ( 3 6 2 9 π ) − i sin ( 3 6 3 1 π ) + 2 i sin ( 3 6 π )
So, the imaginary part is:
Im ( S ) = 4 sin 2 ( 3 6 π ) sin ( 3 6 2 9 π ) − sin ( 3 6 3 1 π ) + 2 sin ( 3 6 π )
Use the sum to product formulas:
Im ( S ) = 4 sin 2 ( 3 6 π ) 2 cos ( 6 5 π ) sin ( − 3 6 π ) + 2 sin ( 3 6 π )
Im ( S ) = 4 sin ( 3 6 π ) 2 + 3
did it a similar way too long enough sigh.
Problem Loading...
Note Loading...
Set Loading...
First note that
cis θ ⇒ cis 2 k − 1 θ = cos θ + i sin θ ⇒ = cos [ ( 2 k − 1 ) θ ] + i sin [ ( 2 k − 1 ) θ ] .
And then
S = k = 1 ∑ 1 5 cis 2 k − 1 ( 3 6 π ) = k = 1 ∑ 1 5 cis [ 3 6 ( 2 k − 1 ) π ] .
If Im [ S ] is the imaginary part of the S then
Im [ S ] = k = 1 ∑ 1 5 sin [ 3 6 ( 2 k − 1 ) π ] . = sin 3 6 π + sin 3 6 3 π + … + sin 3 6 2 9 π .
Multiplying both the sides by − 2 sin 3 6 π
− 2 sin 3 6 π Im [ S ] = − 2 sin 3 6 π sin 3 6 π − 2 sin 3 6 π sin 3 6 3 π − … − 2 sin 3 6 π sin 3 6 2 9 π = − 2 sin 2 3 6 π + [ cos 1 8 2 π − cos 1 8 π ] + [ cos 1 8 3 π − cos 1 8 2 π ] + … … + [ cos 1 8 1 5 π − cos 1 8 1 4 π ] = − 2 sin 2 3 6 π − cos 1 8 π + cos 1 8 1 5 π = − 2 sin 2 3 6 π − cos 3 6 2 π + cos 6 5 π = − 2 sin 2 3 6 π − ( 1 − 2 sin 2 3 6 π ) + cos 6 5 π .
Thus
− 2 sin 3 6 π Im [ S ] Im [ S ] = − 1 − 2 3 = 4 sin 3 6 π 2 + 3 .